2020
DOI: 10.22541/au.158958012.27449923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding  the perceived health outcomes of children during COVID-19 pandemic

Abstract: The study explored the lockdown and quarantine on the perceived psychological distress and other life outcomes of children after the outbreak of COVID-19 in recent past. The study employed the Narrative Thematic Research Design and chose a heterogeneous sample of 20 full-time mothers to report the experiences of the restrictions of their children aged 9-11 years. These mothers were the primary source of data about the impacts of lockdown and quarantine on their children. A telephonic semistructured interview p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…Another study in children with cystic fibrosis in Turkey also did not find a difference in anxiety scores between their patients and age‐matched controls 21 . In the general population, severe stress and traumatizing symptoms in children have been reported in a qualitative study from India and COVID‐19 related restrictions seemed to be the primary cause 22 . This is in line with a previous qualitative report on the 2003 SARS and 2009 H1N1 pandemics, which showed that 30% of children who had been isolated or quarantined met the clinical cut‐off score for post‐traumatic stress disorder 23 .…”
Section: Discussionmentioning
confidence: 92%
“…Another study in children with cystic fibrosis in Turkey also did not find a difference in anxiety scores between their patients and age‐matched controls 21 . In the general population, severe stress and traumatizing symptoms in children have been reported in a qualitative study from India and COVID‐19 related restrictions seemed to be the primary cause 22 . This is in line with a previous qualitative report on the 2003 SARS and 2009 H1N1 pandemics, which showed that 30% of children who had been isolated or quarantined met the clinical cut‐off score for post‐traumatic stress disorder 23 .…”
Section: Discussionmentioning
confidence: 92%
“…The authorities should understand that the recommended strategy of lockdowns and social distancing-which are the need to slow down the spread of the outbreak and protect people from the virus-could have tremendous psychological impacts on people health. The early psychological and mental issues such as disturbance, severe emotional attachment, irritability, fear, resistance, anger, stubborn, frustration, hopelessness, sleeping disorder, and digestive problems in children of China and India due to the COVID-19 lockdowns were observed (Jiao et al, 2020;Tiwari et al, 2020). Also, it is vital to understand the psychological factors that may affect the pandemic related preventative behavior (e.g., news monitoring, social distancing, hygiene) and antisocial behavior (e.g., hoarding supplies) (Oosterhoff, 2020).…”
Section: Behavioral Limitations Of Individuals To Cope With Covid-19mentioning
confidence: 99%
“…Besides, these children also understand the necessity and compulsion of the adherence to the restrictions of the lockdown. It has been suggested that the children of this age group develop some sense of life goals, able to share their positive and negative experiences with their caregivers and reflect some understanding of life realities and broader human collectives (Tiwari, Singh, et al, 2020). In this backdrop, the present study aims to explore the protective roles of joint and nuclear families in shaping the life outcomes of children with age ranging between 9 years to 12 years during the restrictions of COVID-19 through a qualitative research design.…”
Section: Introductionmentioning
confidence: 98%
“…A full-time mother was the incessant primary caregiver from birth to the present (Ahirwar et al, 2019). In some previous studies, collecting data from the parents, especially full-time mothers of younger children have been reported to be useful (Ahirwar et al, 2019;Tiwari, Singh, et al, 2020). The current study chose children between 9 years to 12 years.…”
Section: Introductionmentioning
confidence: 99%